The Effect of Inquiry Learning Model on the Attitudes and Character of High School Students - Astalini; Darmaji; Kurniawan, Dwi Agus; Nawahdani, Ahmad Mansur (Universitas Pendidikan Ganesha, 2024)
Inquiry learning model is one of the choices, to be applied in the teaching and learning process in physics subjects. The problem that arises is the limited or lack of application of the inquiry learning model in learning activities. The purpose of this research is to find out what students' attitudes and character are, and to find out the effect of implementing the inquiry learning model on students' attitudes and character. This type of research is quantitative research with associative and comparative research types. The research sample was students of class XI Science at high school level which consisted of two classes, each class consisting of 26 students. The sampling technique used in this research is purposive sampling technique. The research instrument is a questionnaire in the form of statements, the questionnaire uses a Likert scale. In this research there are three questionnaires, namely a student response questionnaire to the inquiry learning model, a student attitude questionnaire and a student character questionnaire in physics learning. Quantitative data analysis techniques in this research consist of descriptive statistical tests and inferential statistical tests. The findings show that the inquiry learning model can influence students' attitudes and character for the better.